Spondylus and Glycymeris bracelets - Dimitrijević, Vesna (Documenta Praehistorica, 2006)
In the provision, production and exchange of prestigious items and materials in prehistoric Europe, marine shell ornaments play important role. The marine shell collection at the Vinča-Belo Brdo site is the largest in the central and northern Balkans. More than 300 ornament items manufactured from marine shells have been collected since the first excavations in 1908 up until the most recent campaign. The majority of ornaments were made using recent shells that were obtained through trade with contemporaneous Neolithiccommunities; few ornaments were made of fossil bi- valve shells. Bracelets were the most common type. Two bivalve genera, Spondylus and Glycymeris, were used in their production. These are easily recognizable whencomplete valves are compared, but difficult to distinguish in highly modified items where shell morphology is obscured. The defining characteristics for shell identification are presented, particularly to differentiate ornaments manufactured from the Spondylus and Glycymeris genera, as well as those made of recent and fossil shells. The possible exchange routes for these are discussed, as well as their diachronic distribution at the Vinča site.
Keywords: Serbia; Srbija; arheološke najdbe; neolitik; okrasni predmeti; nakit; školjke